A rare case of orbital angioleiomyoma. (2nd January 2021) - Wong, Shiao Wei; Laybourne, James; Irion, Luciane; Cook, Anne
ABSTRACT: A 65-year old woman presented with 3-year history of painless, gradual swelling of the right upper eyelid associated with proptosis. Computed tomography (CT) and magnetic resonance imaging (MRI) of the orbit showed a well circumscribed soft tissue mass in the supero-lateral orbit. An excision biopsy of the lesion was performed via lateral orbitotomy. Histopathology examination and immunochemistry staining confirmed the diagnosis of cavernous angioleiomyoma. The tumour was excised completely. Orbital angioleiomyoma is a rare benign tumour and the lesion can cause visual morbidity, particularly when intraconal. Despite sophisticated imaging modalities, histopathological analysis is essential for diagnosis. Angioleiomyoma should be included in the differential diagnosis of well-defined orbital lesions. Complete surgical excision carries a low risk of recurrence.